2015
DOI: 10.1007/s11786-015-0236-y
|View full text |Cite
|
Sign up to set email alerts
|

Graph Grammars, Insertion Lie Algebras, and Quantum Field Theory

Abstract: Abstract. Graph grammars extend the theory of formal languages in order to model distributed parallelism in theoretical computer science. We show here that to certain classes of context-free and context-sensitive graph grammars one can associate a Lie algebra, whose structure is reminiscent of the insertion Lie algebras of quantum field theory. We also show that the Feynman graphs of quantum field theories are graph languages generated by a theory dependent graph grammar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another work that associates a Lie algebra with a graph grammar is Marcoli and Port (2015) . In this case, the basis Fock space over which the Lie algebra operators are defined is a space of labeled graphs G , rather than labeled graph grammar rules G in → G out , so it is a different and smaller operator Lie algebra than ours.…”
Section: Discussionmentioning
confidence: 99%
“…Another work that associates a Lie algebra with a graph grammar is Marcoli and Port (2015) . In this case, the basis Fock space over which the Lie algebra operators are defined is a space of labeled graphs G , rather than labeled graph grammar rules G in → G out , so it is a different and smaller operator Lie algebra than ours.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, what one means by language and grammar has vastly generalized beyond traditional forms of written language. Examples include graph grammars in graphical languages [57,83], pregroup grammars in diagrammatic languages involving string diagrams [40,77], visual grammars corresponding to compositions involving visual scenes and actions [96,139], and hypergraph / operator algebras that extend graph grammars [4,136,137], just to name a few. In our case here, the collections of objects in both, Obj P and Obj M are not arbitrary collections.…”
Section: States Of Owmentioning
confidence: 99%
“…The unexpected connections to computer science by way of combinatorics hint at a vast untapped potential of interdisciplinary collaboration. So far little research has gone into this direction but articles like [23,24], or [25] -where it was shown that Feynman graphs can be interpreted as a type of formal language generated by a theory dependent graph grammar -seem to suggest that there are deep connections between the two fields whose study might benefit both disciplines.…”
Section: A Different Perspective -Dirac Words As Cartier-foata Monoidsmentioning
confidence: 99%